Radiation Caries and Its Prevention - J. Badalová; Z. Bezrouková (Czech Dental Chamber, 2006)
The paper summarizes a 2.5-year experience in prevention and therapy of radiation caries. The project was focused on the examination, sanation of the teeth and the elaboration of a preventive oral-hygienic program consisting of the care of the patient before, in the course and after the end of a complex antitumor therapy. The cohort included 42 patients, 29 men and 13 women with a newly detected malignity of the orofacial region. The A (collaborating) group included 29 patients, and the B (non-collaboration) one consisted of 13 patients, who were willing to observe preventive measures to less than 50%.In both groups the starting and final values of the KPE, CPI, PLI and PBI indices were compared. The results indicate a statistically significant difference in incidence of caries over the 2.5-year period between the collaborating A group (2.38) and the B group (8.31). There were also significant differences in the values of CPI, PLI and PBI indices indicating compliance of the collaborating group.